(untitled) (Annual of the Faculty of Philosophy in Skopje, 2013)
Social distance that is manifest in ethnic relations is called ethnical and it is typical for the acceptance of members of different ethnic groups in personal and social relationships. It marks integroup attitudes, willingness to connect with various ethnic groups, and the relationship between attitudes towards different ethnic groups. A basic problem of this research is to establish social distance among students from Macedonian and Albanian ethnic origin. The research was conducted on a convenience sample of students from third year the total number of respondents is 251 Macedonian and Albanian students. Analysis of the positions that constructs affecting in the semantic space support the findings obtained for auto stereotypes and hetero stereotypes. Macedonian students of the three factors an most distanced in the semantic space evaluate A Ibanians. The Albanian high school picture is a little bit different. They, though Macedonians perceived as very different or distant from their own ethnic group, as assessed most distanced are the Serbs.